(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article is devoted to methodological approaches for teaching the proper use of glassware in laboratory sessions. It analyzes the types of glassware, their functions, the development of students’ practical skills, and the importance of adhering to safety rules. The article provides recommendations for the effective organization of laboratory sessions within chemistry education and pedagogical practice.